More than just meds: National survey of providers' perceptions of patients' social, economic, environmental, and legal needs and their effect on emergency department utilization - Lia ilona Losonczy; Dennis Hsieh; Chris Hahn; Jahan Fahimi; Harrison Alter (Social Medicine Publication Group, 2014)
Introduction: Emergency departments (EDs) are the safety net for millions of patients who need to access care. Many of these patients have social needs that may influence their healthcare. Methods: We sought to understand ED providers' perceptions of health-related social issues facing their patients by conducting an online survey of emergency medicine physicians nationally. Respondents ranked patients' most common needs, which needs affected healthcare use, and interest in education on these needs. We also queried when needs are assessed and reasons they are not. Responses are reported as proportions, stratified by training level and program type; the chi-square test was used to assess differences between groups. Results: We broadcast survey links to 168 US emergency medicine training programs, receiving 432 responses from 79 different institutions in 31 states; 45% of the respondents were residents and 49% attendings; 47% identified as academic, 28% as county, 18% as community, and 7% as mixed. Providers' ranked factors that influenced ED visits; naming lack of health insurance, homelessness, and transportation problems as several of the top non-medical needs they see in the ED. All respondents replied that they care for patients with social needs; all but two felt that social needs move patients to return to the ED. While providers consistently ask about social needs, for any specific social need the number of doctors who routinely ask ranges from 61-100% depending on need. Reasons for not asking included feeling unable to act, lack of time, and lack of knowledge. Only a small minority felt that addressing non-medical needs was not part of their job or that needs were not relevant to patients' health. Most providers (80%) would like more resources and 70% reported they would attend educational sessions if they were available. We found no difference between attendings and residents in interest in attending educational sessions or in the percentage who ask about needs. Providers from all types of institutions were equally likely to believe social needs caused patients to return and to ask about such needs. Conclusions: This study highlights the fact that emergency department providers around the country see a large number of social needs. They identified specific needs that increase the utilization of healthcare services. These needs would more likely be addressed if greater referral resources were available.